Functionality of corn and sorghum proteins in visco-elastic dough systems - Smith, Brennan M. (Kansas State University, 2012)
Zein, the storage protein of corn, has been shown to form a wheat-like dough; however the exact mechanism is unknown since zein lacks the large polymeric proteins found in wheat. To understand how zein forms a dough, different reagents were added during mixing of zein. Salts from the Hofmeister series were used to determine how hydrophobic interactions influence zein’s dough forming ability. In addition, urea, ethanol, and beta mercaptoethanol (β-ME) were also tested to evaluate the effects of protein denaturation and disulfide bonds on zein dough formation and bread quality. Kosmotropic salts had a negative effect on zein dough formation indicating that increasing hydrophobic interactions prevented dough formation. Surface hydrophobicity was found to decrease significantly (p < 0.05) when zein was exposed to 1M or 2M of the kosmotropic salts. Conversely, chaotropic salts had a slight positive effect on zein dough formation as did urea and ethanol. Interestingly, -ME had little effect on zein dough formation demonstrating that disulfide bonds played no role in zein dough development, and that large disulfide linked polymeric protein complexes were not present as found in wheat dough. Specific volumes of zein-starch bread increased as NaCl content in the bread formula decreased. Likewise, including 5% ethanol (v/v) in the bread formula was found to increase bread quality. Experiments were also conducted to compare the functionality of isolated sorghum proteins (kafirins) to commercially available zein produced during wet milling of corn. The effect of steeping, the first step in wet milling, on kafirin functionality was investigated. Sorghum flour was steeped for 0, 72, or 96 hours. Unsteeped sorghum flour was digested with Alcalase for 90 min at 50°C. After steeping or digestion with Alcalase, kafirins were isolated from the remaining material. Both groups of Kafirins had the ability to form a zein-like visco-elastic resin when mixed with warm water by hand. This is the first time that kafirin has been reported to form a visco-elastic resin using only water as a plasticizer.
Keywords: Gluten-free; Maize; sorghum; Zein; kafirin; protein; Food Science (0359)